233k views
24 votes
Solve the following system of equations using the substitution method.

The problem- y= -2x+11
3x + y = 18

User Danja
by
5.7k points

1 Answer

8 votes

Answer:

x = 7

y = -3

Explanation:

the first equation is already solved for 'y' so we can substitute '-2x+11' for 'y' in second equation

3x + (-2x + 11) = 18

x + 11 = 18

x = 7

solve for 'y'

y = -2(7) + 11

y = -14 + 11

y = -3

User Rocking Chief
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.